Anti-granulocyte opsonic activity and autoimmune neutropenia. - Hadley, A; Holburn, A; Bunch, C; Chapel, H (1986)
Sera from patients with unexplained neutropenia have been assayed for anti-granulocyte opsonic activity using a chemiluminescence technique which measures the metabolic response of human monocytes to antibody-coated granulocytes. This rapid and simple technique was more sensitive than indirect immunofluorescence in the detection of anti-granulocyte antibodies. Anti-granulocyte opsonic activity was detected in sera from 17 of 31 patients, suggesting that their neutropenia may have had an autoimmune basis. The opsonic activity of five of the 17 sera was increased when granulocytes were sensitized in the presence of fresh serum. Four of these sera bound IgM and C3b to granulocytes in the immunofluorescence test. Human IgG when added to the monocyte suspension medium inhibited monocyte response to IgG antibody-opsonized granulocytes. This inhibition was less when granulocytes were opsonized with sera containing IgM and complement granulocyte-binding activity. This observation may be relevant to the selection of neutropenic patients for therapeutic use of intravenous immunoglobulin.